African-American Life in Clay County - Lienberger, William (Kansas State University, The Chapman Center for Rural Studies, 2014)
This paper explores the agricultural history of Clay County, Kansas, and the African American workers who persevered during the time. Sources used were newspaper articles, the class reader, websites, and a book about Broughton, Kansas.
William Lienberger, “African-American Life in Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/228.
Keywords: African Americans; Clay Center; Clay County; Harvey Ramsey; Kansas; William Lienberger